2016
DOI: 10.1109/tste.2016.2535327
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Estimation of the Flicker Level Induced by Wave Energy Farms

Abstract: Wave energy farms may cause voltage flicker on the local grid to which they will be connected due to the strong fluctuations that their output power may present. IEC standard 61400-21 describes methods for estimating the flicker level for different short-circuit ratios as well as for different numbers of devices composing the farm. This method was initially developed for wind farms but is applicable to wave energy farms as well. However, besides the short-circuit ratio and the number of devices composing the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…where the percentiles P 0.1 , P 1 , P 3 , P 10 , and P 50 are the flicker levels exceeded for 0.1%, 1%, 3%, 10%, and 50% of every 10-min interval, respectively. They reflect the ratio of the relative voltage difference (DV = V max 2 V min ) to the base voltage (V) (Alaboudly et al, 2013;Blavette et al, 2016;Chen et al, 2016). P lt is measured as an average of 12 values of P st levels over a 2-h duration using (5) as…”
Section: Voltage Flickermentioning
confidence: 99%
See 1 more Smart Citation
“…where the percentiles P 0.1 , P 1 , P 3 , P 10 , and P 50 are the flicker levels exceeded for 0.1%, 1%, 3%, 10%, and 50% of every 10-min interval, respectively. They reflect the ratio of the relative voltage difference (DV = V max 2 V min ) to the base voltage (V) (Alaboudly et al, 2013;Blavette et al, 2016;Chen et al, 2016). P lt is measured as an average of 12 values of P st levels over a 2-h duration using (5) as…”
Section: Voltage Flickermentioning
confidence: 99%
“…Its main causes are abrupt changes in the power consumption of large-capacity loads (electrical arc furnaces, etc.) in the system (Alasooly and Redha, 2010;Blavette et al, 2016) and inrush current at the startup of induction machines (Chen et al, 2016;Leinonen and Laketic, 2018;Rahman et al, 2018), but it is recognized that severe output variation of wind power may also be another cause of voltage flicker (Ammar and Ammar, 2016). Thus, studies to analyze the voltage flicker caused by large-scale WTs have been conducted under numerical simulations (Alaboudly et al, 2013;Ammar and Ammar, 2016;Fooladi and Akbari Foroud, 2016;Hu et al, 2009;Mascarella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If sufficient storage is employed with wave farms, the flicker level, and other power quality issues, may be significantly decreased. Flicker estimation, using various assessment tools for wave farms, are discussed in [48,49].…”
Section: Impacts Of Wave Energy On Existing Gridsmentioning
confidence: 99%
“…By arranging the park layout such that the WECs are not excited simultaneously by the incident waves, the power output can be further smoothened (Engström et al, 2013;Sjolte et al, 2013;Göteman et al, 2014). Armstrong et al (2015), Kovaltchouk et al (2016), and Blavette et al (2016) used approximate methods for hydrodynamics and power production in the array to study flicker severity with a focus on transmission and grid aspects. The impact of a park consisting of ten OWCs and ten heaving buoys on the transmission system was studied by Armstrong et al (2015), and it was concluded that the transformers and transmission lines would remain below 45% capacity.…”
Section: Delivering Grid-compatible Electricitymentioning
confidence: 99%
“…Kovaltchouk et al (2016) studied limits to voltage fluctuations for arrays of different WEC types, and compensatory actions were proposed to allow grid integration. Blavette et al (2016) estimated the flicker level as a function of grid impedance angle. Hydrodynamics and electro-mechanic aspects were included in the works by Tedeschi and Santos-Mugica (2013) and Parwal et al (2018).…”
Section: Delivering Grid-compatible Electricitymentioning
confidence: 99%